Gastrointestinal stromal tumor causing ileo-ileal intussusception in an adult patient a rare presentation with review of literature - Gupta, Amit (African Field Epidemiology Network, 2011)
Gastrointestinal stromal tumors (GIST) are mesenchymal tumors occurring anywhere along the gastrointestinal tract and are believed to originate from the interstitial cells of Cajal. They commonly arise in the stomach or small intestine. The usual growth pattern is exophytic invading adjacent organs or perforation into the peritoneal cavity which may result in bleeding or obstructive symptoms. Intussusception and obstruction is a very uncommon presentation of these lesions because of their tendency to grow in an extraluminal fashion. We report an unusual case of 59 yrs old man presenting with acute small bowel obstruction, which on exploration was found to be due to ileo-ileal intussusception and the lead point of intussusception was a tumor, which was histologically diagnosed as GIST